2019
DOI: 10.3389/fendo.2019.00855
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a Family History of Diabetes and Rapid eGFR Decline in Patients With Type 2 Diabetes and Biopsy-Proven Diabetic Kidney Disease

Abstract: Objective: This study aimed to identify the risk factors for a rapid decline in the estimated glomerular filtration rate (eGFR) in Chinese patients with type 2 diabetes and biopsy-proven diabetic kidney disease (DKD). Method:This was a retrospective cohort study. Patients with biopsy-proven DKD who had been followed-up for at least 1 year were enrolled. Baseline clinicopathological data and serum creatinine levels that had been measured at least three times during follow-up in our hospital were collected. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In our study, early-onset group presented higher proportion of DM family history, which was similar with previous studies [ 27 , 28 ]. A past study of our group also showed that patients with DN and family history of DM had more aggressive renal disease and rapidly falling in eGFR [ 29 ]. Other unknown factors remain further exploration.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, early-onset group presented higher proportion of DM family history, which was similar with previous studies [ 27 , 28 ]. A past study of our group also showed that patients with DN and family history of DM had more aggressive renal disease and rapidly falling in eGFR [ 29 ]. Other unknown factors remain further exploration.…”
Section: Discussionmentioning
confidence: 86%
“…DN was defined according to the standard reported by An et al [ 18 ] in 2015 and was diagnosed by at least two renal pathologists and/or nephrologists based on the Renal Pathology Society (RPS) classification [ 19 ]. To accurately characterize trajectories of eGFR decline, we restricted our analysis to the following patients according to our previous study [ 20 ]: (1) those in whom serum creatinine levels were measured at least three times per year during the follow-up period; and (2) all serum creatinine assays were performed at our hospital to minimize methodological differences. Therefore, the exclusion criteria were: (1) coexisting non-diabetic kidney disease and systemic diseases, especially those involving antineutrophil cytoplasmic antibodies, such as vasculitis, antiglomerular basement membrane disease, and lupus nephritis; (2) nontype 2 diabetes; (3) progression to ESRD before renal biopsy; and (4) lack of trajectory of eGFR decline because serum creatinine levels were measured less than thrice annually at our hospital or performed at other hospitals (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“… 27 A recent study also showed that a family history of diabetes is an independent risk factor for rapid decline of eGFR in patients with DN. 28 We found that patients with a family history of diabetes are more likely to have adverse renal outcomes, suggests that the genetic background and lifestyle of diabetes may be related to the rapid decline of renal function in patients with DN.…”
Section: Discussionmentioning
confidence: 75%